Risk, failure, play what dance reveals about martial arts training - O'Shea, Janet 1968- (New York, NY, United States of America Oxford University Press, 2019)
Risk, Failure, Play illuminates the many ways in which competitive martial arts writer differentiate themselves from violence. Presented from the perspective of a dancer and writer, this book takes readers through the politics of everyday life as experienced through training in a range of martial arts practices such as jeet kune do, Brazilian jiu jitsu, kickboxing, Filipino martial arts, and empowerment self-defense. author Janet O'Shea shows how play gives us the ability to manage difficult realities with intelligence and demonstrates that physical play, with its immediacy and heightened risk, is particularly effective at accomplishing task. Risk, Failure, Play intertwines personal experience with phenomenology, social psychology, dance studies, performance studies, as well as theories of play and competition in order to produce insights on pleasure, mastery, vulnerability, pain, agency, individual identity, and society. Ultimately, this book suggests that play allows us to rehearse other ways to live that the ones we see before us and challenges us to reimagine our social reality
No hard feelings : why martial arts doesn't mean what violence means -- The magic ring : how combat sport transforms meaning through space and movement -- Chess with cardio : finding the meeting point in sport fighting -- What's there to lose? : vulnerability in combat sport -- On the line : the pleasure of risk versus the culture of fear -- Fail better : the paradox of defeat in martial arts training -- Making play work : competition, spectacle, and perfection in sport -- Making work play : rethinking competitive pleasure through self- -- Defense training
Includes bibliographical references and index
Keywords: Martial arts -- Psychological aspects; Martial arts -- Social aspects